Aspirin and the risk of nondigestive tract cancers: An updated meta‐analysis to 2019. Issue 6 (6th October 2020) - Santucci, Claudia; Gallus, Silvano; Martinetti, Marco; La Vecchia, Carlo; Bosetti, Cristina
Abstract: Aspirin has been associated with a reduced risk of colorectal and other selected digestive tract cancers, but the evidence for other neoplasms is still controversial. To provide an up‐to‐date quantification of the role of aspirin on lung, breast, endometrium, ovary, prostate, bladder, and kidney cancer, we conducted a systematic review and meta‐analysis of all observational studies published up to March 2019. We estimated pooled relative risk (RR) of cancer or cancer death for regular aspirin use vs non‐use by using random‐effects models, and, whenever possible, we investigated dose‐ and duration‐risk relations. A total of 148 studies were considered. Regular aspirin use was associated to a reduced risk of lung (RR = 0.88, 95% confidence interval [CI] = 0.79‐0.98), breast (RR = 0.90, 95% CI = 0.85‐0.95), endometrial (RR = 0.91, 95% CI = 0.84‐0.98), ovarian (RR = 0.91, 95% CI = 0.85‐0.97) and prostate (RR = 0.93, 95% CI = 0.89‐0.96) cancer. However, for most neoplasms, nonsignificant risk reductions were reported in cohort and nested case‐control studies and there was between‐study heterogeneity. No association was reported for bladder and kidney cancer. No duration‐risk relations were observed for most neoplasms, except for an inverse duration‐risk relation for prostate cancer. The present meta‐analysis confirms the absence of appreciable effect of regular aspirin use on cancers of the bladder and kidney and quantifies small and heterogeneous inverse associations for other cancers considered. What's new?: Aspirin use has been associated with a reduced risk of colorectal and other digestive tract cancers. A favorable effect of aspirin has also been reported for a few other common neoplasms, but the evidence is still controversial. This comprehensive meta‐analysis on aspirin use and non‐digestive tract cancers confirms the absence of any meaningful association with bladder and kidney cancer risk and reports small and heterogeneous inverse associations with cancers of the lung, breast, endometrium, ovary, and prostate. Moreover, there were no duration‐risk relations for most neoplasms, except an inverse duration‐risk relation for prostate cancer.